1998
DOI: 10.1016/s0377-1237(17)30539-7
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight Babies : Incidence and Risk Factors

Abstract: In a prospective hospital based study, during the period from Jan 95 to Dec 96, 3100 consecutively delivered live newborns were studied for the incidence of low birth weight neonates and to evaluate the associated risk factors. One thousand fourteen newborns were classified as low birth weight babies. The incidence expressed per 1000 live births was 327 (32.7%). Of these, 815 (80.4%) were small for gestational age neonates and 199 (19.6%) were preterm neonates. Five hundred seventy small for gestational age ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
5
5
0
Order By: Relevance
“…[9] In present study, maximum percentage of LBW babies was observed in two extreme of ages, i.e., below 20 and in mothers above 30 years of age. Findings of present study were comparable with the findings of Raman et al [10] and Negi et al, [11] who observed the similar relationship between age of mother and birth weight. It shows probability of LBW increases in two extreme of ages, i.e., below 20 and in mothers above 30 years of age.…”
Section: Discussionsupporting
confidence: 93%
“…[9] In present study, maximum percentage of LBW babies was observed in two extreme of ages, i.e., below 20 and in mothers above 30 years of age. Findings of present study were comparable with the findings of Raman et al [10] and Negi et al, [11] who observed the similar relationship between age of mother and birth weight. It shows probability of LBW increases in two extreme of ages, i.e., below 20 and in mothers above 30 years of age.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the maximum percentage of LBW babies were born to mothers with age <20 years (57.1%), which is comparable with the studies done by Agarwal et al, [5] Raman, [8] and Negi et al, [9] who also observed that the prevalence of LBW was more among mothers with age <20 years.…”
Section: Discussionsupporting
confidence: 90%
“…The results were consistent with various other studies who also observed that the prevalence of LBW was more among mothers with age <20 years. [12][13][14][15] Regarding the educational status, 80% of them were educated up to class 12 in the present study, similar findings were found in various other studies. 16,17 Majority of the study subjects were house wife's in the present study, similar results were obtained in study conducted by Kandhasamy et al 6 Majority of them belonged to class 3 SES in the present study, similar results were obtained in study conducted by Kandhasamy et al and Rajashree et al 6,12 This study found that around 60% of the study subjects had <2 ante natal visits which was similar to the findings of study conducted by Kandhasamy et al and Malik et al, where in those mothers who had received less than four ANC visits had a significant risk of having LBW.…”
Section: Discussionsupporting
confidence: 90%